Volba optimálního portfolia cenných papírů jakožto investiční hlavolam - Bradová, Klára (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Teorie portfolia je mikroekonomická disciplína zabývající se zkoumáním kapitálových trhů a aktiv, která se na nich obchodují. Tato diplomová práce je zaměřena na volbu optimálního portfolia cenných papírů, konkrétně akcií. Cílem je najít výsledné portfolio splňující dané požadavky. První část práce uvádí teorii potřebnou pro následný praktický případ sestavení optimálního portfolia. Druhá část je věnována samotným výpočtům vedoucím k nalezení portfolia s požadovanou výnosností.

The portfolio theory is microeconomic discipline which deals with the exploration of capital markets and assets that are traded on them. This diploma thesis is focused on optimal stock portfolio selection. The main aim is to find a final portfolio fulfilling the requirements. The first part provides the theory needed for the subsequent establishment of a practical case of the optimal portfolio. The second part is devoted to the actual calculations leading to finding the portfolio with the desired rate of return.
Optimal Stock Portfolio Selection as an Investment Conundrum
Keywords: Teorie portfolia; cenné papíry; optimalizace; burza; akcie; očekávaná výnosnost; riziko; Portfolio theory; securities; optimization; stock market; stock; expected return; risk